Determinants of Learning Satisfaction in Technology-Integrated Higher Education: The Role of Digital Competence and Self-Regulated Learning - Habibi, Akhmad; Hendra, Robi; Sari, Liza Puspita (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
The integration of digital technologies into higher education has transformed instructional practices and reshaped determinants of student learning satisfaction. This study investigates the influence of self-efficacy, academic service quality, digital competence, and self-regulated learning on student satisfaction within a technology-integrated biology education context. A quantitative survey design was employed involving 155 undergraduate students selected from a population of 360 students at a public university in Indonesia. Data were collected using a five-point Likert-scale questionnaire and analysed through PLS-SEM. The measurement model demonstrated satisfactory reliability and validity, with all constructs meeting the required thresholds for factor loadings, composite reliability, and average variance extracted. The structural model revealed that academic service quality (β = 0.361, p < 0.05) and self-regulated learning (β = 0.516, p < 0.001) significantly and positively predicted student satisfaction. In contrast, self-efficacy and digital competence did not exhibit significant direct effects. The model explained 85.7% of the variance in learning satisfaction (R² = 0.857), indicating strong predictive capacity. These findings suggest that within technology-integrated higher education environments, students’ capacity to regulate their learning processes and the quality of institutional academic services play more decisive roles in shaping satisfaction than technical digital skills alone. The study contributes empirical evidence to the discourse on technology-enhanced pedagogy by emphasizing the strategic importance of self-regulation and institutional service systems in optimizing digitally mediated learning experiences.